Chemoenzymatic Cascade Synthesis of Optically Pure Alkanoic Acids by Using Engineered Arylmalonate Decarboxylase Variants. Issue 19 (12th March 2019) - Enoki, Junichi; Mügge, Carolin; Tischler, Dirk; Miyamoto, Kenji; Kourist, Robert
Abstract: Arylmalonate decarboxylase (AMDase) catalyzes the cofactor‐free asymmetric decarboxylation of prochiral arylmalonic acids and produces the corresponding monoacids with rigorous R selectivity. Alteration of catalytic cysteine residues and of the hydrophobic environment in the active site by protein engineering has previously resulted in the generation of variants with opposite enantioselectivity and improved catalytic performance. The substrate spectrum of AMDase allows it to catalyze the asymmetric decarboxylation of small methylvinylmalonic acid derivatives, implying the possibility to produce short‐chain 2‐methylalkanoic acids with high optical purity after reduction of the nonactivated C=C double bond. Use of diimide as the reductant proved to be a simple strategy to avoid racemization of the stereocenter during reduction. The developed chemoenzymatic sequential cascade with use of R ‐ and S ‐selective AMDase variants produced optically pure short‐chain 2‐methylalkanoic acids in moderate to full conversion and gave both enantiomers in excellent enantiopurity (up to 83 % isolated yield and 98 % ee ). Abstract : A chemoenzymatic cascade : By combining enzymatic decarboxylation and subsequent diimide‐mediated C=C double bond reduction optically pure short‐chain 2‐methylalkanoic acids are formed (see Scheme). This route exploits the outstanding enantioselectivity and capacity of bacterial arylmalonate mutants to produce both enantiomers in pure form.